2009
DOI: 10.1186/1472-698x-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lankan tsunami refugees: a cross sectional study of the relationships between housing conditions and self-reported health

Abstract: BackgroundOn the 26th December 2004 the Asian tsunami devastated the Sri Lankan coastline. More than two years later, over 14,500 families were still living in transitional shelters. This study compares the health of the internally displaced people (IDP), living in transitional camps with those in permanent housing projects provided by government and non-government organisations in Sri Lanka.MethodsThis study was conducted in seven transitional camps and five permanent housing projects in the south west of Sri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Similar concerns have been expressed in other recent studies, indicating that competition, housing anxiety and bufferzone implementation have resulted in obstacles to equitable rebuilding of houses and livelihoods [32], as well as the need for further beneficiary and lo- cal-network feedback in disaster planning [33,34], and the need for specific interventions to address the health inequalities that internally displaced peole living in transitional camps reported [35]. However, the present study indicated that while the Sinhalese mentioned injustices and accounted for them in terms of corruption or preferential treatment, both the Muslim and Hindu Tamil-speaking people pointed to ethnic discrimination, which they also invoked for the lack of solidarity.…”
Section: Discussionsupporting
confidence: 55%
“…Similar concerns have been expressed in other recent studies, indicating that competition, housing anxiety and bufferzone implementation have resulted in obstacles to equitable rebuilding of houses and livelihoods [32], as well as the need for further beneficiary and lo- cal-network feedback in disaster planning [33,34], and the need for specific interventions to address the health inequalities that internally displaced peole living in transitional camps reported [35]. However, the present study indicated that while the Sinhalese mentioned injustices and accounted for them in terms of corruption or preferential treatment, both the Muslim and Hindu Tamil-speaking people pointed to ethnic discrimination, which they also invoked for the lack of solidarity.…”
Section: Discussionsupporting
confidence: 55%
“…12 Older age was associated with coughs, colds and fever in an urban livelihood study conducted in Dhaka slums, 25 and the prevalence of coughs was higher among women compared to men in transitional camps in Sri Lanka. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Common communicable diseases in an emergency include diarrheal disease and cholera, infection, meningitis, measles, malaria and respiratory diseases. Not only overcrowded shelters are considered one of the most influential factors in the spread of communicable diseases (Turner et al 2009 ; Alnsour and Meaton 2014 ), but also the presence of mould and damp due to poor air quality can contribute to the incidence of communicable diseases among refugee populations. Physical diseases associated with mental health are also increasing and the impact of mental illness is considered more significant amongst displaced populations (Cardozo and Mollica 2018 ) than in the rest of society.…”
Section: Comparative Analysismentioning
confidence: 99%